Counterexpectational but sentences in European Portuguese - Nádia Canceiro (Études romanes de Brno)
European Portuguese, French and English differ from languages as Spanish or German in that they only have one adversative conjunction. Cases like that of Portuguese are referred to in the literature as ambiguous because one conjunction conveys several values (Horn 2001), such as contrast, correction or denial of expectations. In this paper, we propose contrast as the basic value of mas ('but', in English) and will analyze its subvalue of denial of expectations, looking at how this reading is established in adversative sentences, what is meant by expectation, the pragmatic implicatures associated with these constructions and, finally, the syntactic structure that underlies them.